(untitled) (Al-Academy, 2021)
The paper studies the science of “Biomimicry” or imitation of nature, and how to utilize it to create contemporary designs. It starts by defining biomimicry and innovation. Then, the style of imitating nature is highlighted, which is considered one of the most important methods of innovation. It includes simulating animals and plants (in their environmental conditions) to use the natural and dynamic design solutions to produce innovative designs, that enhance the concept of sustainability. Various forms of natural species are presented, to show their benefit in contemporary metal product designs. Finally, a model of a metal lighting unit is developed, where innovative ideas inspired by silkworm cocoon are used in its design. The study concluded that Biomimicry offers many innovative and sustainable design solutions, through the aesthetic values presented by nature. Theses design solutions can be applied to metal and artistic products in general which are efficient and sustainable.